Kendali Motor Stepper pada Fast Shot & Slow Shot Valve Die Casting Machine Menggunakan PLC Omron - Muntashir, Abdillah Aziz; Rizky, Muhammad Ario; Nugroho, Muhammad Samhadi (JURNAL INTEGRASI, 2023)
In producing a product in the industry, it is necessary to pass a series of processes, one of which is in the printing process or die casting. After installation of casting molds (Fix Dies & Moving Dies), it is necessary to set the fast shot & slow shot valve rotation to determine the amount that pushes the molten liquid into the mold, so the casting machine is ready to use. At this time the Fast Shot & Slow Shot Valve setting process is still done manually (conventional), the technician must make a rotation manually and only look at the value of the needle available on the knob, therefore we need a modification on the control system that can facilitate in doing setting the valve. By using the Stepper motor Nema 17 as the output of the Omron CP1L-M30DT-D PLC and also using Encoder E6B2-CWZ6C as an input that has been calibrated, so that the round reading can be seen in HMI Omron NB7W-TW00B. Obtained a fast cycle time results, namely in moving 1 round of knob, it takes 0.6 seconds.